(untitled) (ENTHYMEMA, 2011)
This article outlines the bases of a novel’s epistemology, answering to basic questions such as: what and how can we get to know through the novel? Starting from a definition of the novel as a piece of fictional narrative, we will develop a position of radical cognitivism, which entails that the novel (a) produces modal knowledge; (b) validates this knowledge by means of the principle of verisimilitude; (c) facilitates the learning process through experience by virtue of imaginative exemplification. The theses proposed here are confirmed with reference to recent experimental dates from cognitive sciences, more specifically from cognitive psychology, about imagination, fiction, and simulation.